2021
DOI: 10.33808/clinexphealthsci.817535
|View full text |Cite
|
Sign up to set email alerts
|

Symptoms and Care Satisfaction in Patients Who Underwent Coronary Artery Bypass Graft Surgery

Abstract: Objective: This study was conducted to investigate of symptoms and care satisfaction in patients who had a coronary artery bypass graft (CABG) surgery. Methods:The study population consisted of patients who had a coronary artery bypass graft surgery in a public and a foundation hospital in Istanbul between December 2018 and May 2019 and the study sample 176 patients who met the inclusion criteria and agreed to take part in the study. The study data were collected using the self-report method with the help of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
1
2
0
Order By: Relevance
“…Similar findings were presented by Sayin et al The satisfaction evaluation was lower in patients who underwent a serious surgery, experienced pain, and movement or nutrition limitations [29]. Post-surgical pain, lack of appetite, nausea, and post-CABG wound symptoms also correlated negatively with satisfaction in Bozkurt and Saglam [31]. Similarly, Sillero and Zabalegui, who measured the satisfaction of surgical patients with perioperative nursing care, also showed that patients with high levels of pain had lower satisfaction with nursing care, and the recovery process of pain slowed down [27].…”
Section: Experience and Satisfaction With Nursing Care Vs Sociodemogr...supporting
confidence: 78%
See 1 more Smart Citation
“…Similar findings were presented by Sayin et al The satisfaction evaluation was lower in patients who underwent a serious surgery, experienced pain, and movement or nutrition limitations [29]. Post-surgical pain, lack of appetite, nausea, and post-CABG wound symptoms also correlated negatively with satisfaction in Bozkurt and Saglam [31]. Similarly, Sillero and Zabalegui, who measured the satisfaction of surgical patients with perioperative nursing care, also showed that patients with high levels of pain had lower satisfaction with nursing care, and the recovery process of pain slowed down [27].…”
Section: Experience and Satisfaction With Nursing Care Vs Sociodemogr...supporting
confidence: 78%
“…However, clinical hospital patients achieved higher scores for satisfaction (79.86 ±19.31), and a statistically significant difference was reported between the average satisfaction score and level of education, chronic diseases, type of hospitalization, or the number of patients in a room [30]. The average satisfaction score among CABG patients was at a moderate level (52.87 ±22.54) [31]. Higher scores were achieved by Gezer and Arslan researching one-day clinic patients, who graded satisfaction at 82.4 ±19.2 and experience at 84.4 ±18.1 on average.…”
Section: Experience and Satisfaction With Nursing Care Vs Sociodemogr...mentioning
confidence: 92%
“…According to the literature, patients undergoing cardiac surgery experience pain-related movement constraints, 32 insomnia, 43 loss of appetite, 44 and difficulty breathing. 32 In parallel with the literature, patients, caregivers and nurses in our study agreed that patients' daily living activities were restricted after surgery.…”
Section: Effect Of Pain On Activities Of Daily Livingmentioning
confidence: 99%